NATURE-BASED LEARNING FOR DEVELOPING THE ISLAMIC POTENTIAL OF STUDENTS AT AL FAZZA NATURAL ELEMENTARY SCHOOL, DEPOK - Putra, Fajar Harguna Endra (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
Nature-based learning is an educational approach that utilizes the surrounding environment as a source of learning. The nature-based learning approach is designed to integrate Islamic values ​​with nature exploration activities so that it can form religious character, love for the environment, and intellectual abilities of students. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. This study aims to analyze the implementation of nature-based learning in developing the potential of Islamic students at Al Fazza Elementary School, Depok. The results of the study indicate that nature-based learning at Al Fazza Elementary School prioritizes the principle of monotheism in every learning activity, such as observing natural phenomena, practicing farming, and project-based thematic learning. In addition, this method is effective in building an attitude of environmental care, discipline, cooperation, and spiritual appreciation of students.